Screening for hepatitis C at the emergency department: Should babyboomers also be screened in Belgium?. (20th December 2018) - Bielen, Rob; Kremer, Cécile; Koc, Özgür M.; Busschots, Dana; Hendrickx, Diana M.; Vanelderen, Pascal; Hens, Niel; Nevens, Frederik; Robaeys, Geert
Abstract: Background & Aims: Patients are not screened adequately for hepatitis C virus infection in Belgium. In the USA, the Center for Disease Control recommends screening for patients born in the babyboom period (1945‐1965). In Europe, the babyboom cohort was born between 1955 and 1974, but no screening policy has been targeted to this group. We aimed to study the prevalence of hepatitis C virus in an emergency department population in Belgium and the risk factors associated with hepatitis C virus infection. Method: We performed a monocentric, cross‐sectional seroprevalence study between January and November 2017 in a large Belgian non‐university hospital. Patients aged 18‐70 years presenting at the emergency department were eligible. Patients completed a risk assessment questionnaire and were screened for hepatitis C virus antibodies (Ab) with reflex hepatitis C virus ribonucleic acid testing. Results: Of 2970 patients, 2366 (79.7%) agreed to participate. hepatitis C virus Ab prevalence was 1.31%. Twenty‐one (67.7%) hepatitis C virus Ab‐positive patients were born between 1955 and 1974. With a previous treatment uptake of 54.5%, the prevalence of viremia was 0.9% in retrospect; 0.2% were newly diagnosed. The weighted multiple logistic regression model identified males born in the 1955‐1974 cohort, intravenous drug use and high endemic birth country as significant risk factors for hepatitis C virus infection ( P < 0.05). Conclusion: Although the prevalence of hepatitis C virus Ab at the emergency department was higher than previously estimated for the general population in Belgium, the number of newly diagnosed patients with viremia was low. To optimize screening strategies, screening should be offered to males born in the 1955‐1974 cohort, but especially in drug users, the prison population and immigrants from high endemic countries.